Prostatic artery embolization (PAE) for prostatic origin bleeding in the context of prostate malignancy. (June 2019) - Tapping, Charles R; Crew, Jeremy; Proteroe, Andrew; Boardman, Phil
Prostate artery embolization (PAE) has been shown to be beneficial in treating men with benign prostatic hypertrophy (BPH). Here we describe treating four patients with prostate cancer (two with organ-confined and two with metastatic prostate cancer) with prostatic bleeding with PAE. Patients had other causes of hematuria excluded and were followed up at 3, 12, and 18 months after PAE. All four cases were technically successful and all cases of hematuria had resolved by the three-month follow-up (100%). There was one case of recurrence at 13 months after PAE which was successfully treated. PAE is useful for controlling significant prostatic bleeding in patients with prostate cancer and improves quality of life. Patients may, however, need repeated treatments to control the bleeding.